Information and Communication Technology-Based Learning Innovation in the Covid-19 Pandemic Era - Fathima, Siti (Journal of Strategy and Transformation in Educational Management, 2024)
This article discusses the challenges and opportunities arising from the COVID-19 pandemic in the education sector, especially regarding information and communication technology (ICT) to support online learning. This article also outlines some learning innovations by various parties, such as governments, educational institutions, teachers, and students, to overcome barriers and harness the potential of ICT in online learning. In addition, this article also provides several recommendations to improve network quality and accessibility website learning in Indonesia, such as strengthening digital learning content and platforms, developing students' and teachers' digital skills, and expanding digital connectivity for schools across the country.